The Fables of La Fontaine - Jean De La Fontaine
This book brings together over one hundred of Jean de La Fontaine's best-loved fables for children, in a magnificent new English translation by C. J. Moore (author of In Other Words: A Language Lover's Guide to the Most Intriguing Words Around the World). There are full colour illustrations throughout. Borrowing his inspiration and material unashamedly from Aesop's fables, La Fontaine wrote his stories in French verse in the latter half of the seventeeth century, and they have been popular classics ever since. Timeless stories of countryfolk, heroes from Greek mythology and familiar creatures, each tale contains a moral for living, just as relevant today as 300 years ago. Fables in this collection include favourites such as The Tortoise and the Hare, The Grasshopper and the Ant, and The Raven and the Fox.